2019
DOI: 10.3390/soc9020046
|View full text |Cite
|
Sign up to set email alerts
|

Denying the Darkness: Exploring the Discourses of Neutralization of Bundy, Gacy, and Dahmer

Abstract: This exploratory study analyzed how three serial killers (i.e., Bundy, Gacy, and Dahmer) potentially rationalized and justified their murders by applying techniques of neutralization. This paper discusses how the use of these neutralizations also functions as a form of stigma management assisting in the maintenance of a positive presentation of self, thus mitigating responsibility for their crimes. This study conducted a content analysis of data comprised from interviews and case histories of these three seria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 65 publications
(241 reference statements)
0
2
0
Order By: Relevance
“…Samuel Little is now believed to be the most prolific serial killer in American history. At this time, it has already been confirmed that he has killed over 50 women, and it is generally believed that he may have killed closer to 100 during his 35-year reign of terror (Holcombe, 2019;Palazzolo, 2019). Little has become the quintessential example of a sadipathic killer.…”
Section: Appurtenant Literature Reviewmentioning
confidence: 91%
“…Samuel Little is now believed to be the most prolific serial killer in American history. At this time, it has already been confirmed that he has killed over 50 women, and it is generally believed that he may have killed closer to 100 during his 35-year reign of terror (Holcombe, 2019;Palazzolo, 2019). Little has become the quintessential example of a sadipathic killer.…”
Section: Appurtenant Literature Reviewmentioning
confidence: 91%
“…Serial murder refers to the killing of at least three or more people across a period of time (Bartels & Parsons, 2009). In the literature, it is commonly stated that there needs to be a "cooling off" period between killings to qualify as serial murder (James, 2019). For example, if a person committed three murders across a single afternoon, in different locations, this would be viewed as a single episode.…”
Section: Literature Reviewmentioning
confidence: 99%